2020
DOI: 10.1002/slct.202000748
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐Doped Graphene Oxide as a Sustainable Carbonaceous Catalyst for Greener Synthesis: Benign and Solvent‐free Synthesis of Pyranopyrazoles

Abstract: The development of benign strategies using the greener catalytic system is one of the prime tasks to improvise the greenness and sustainability in the synthesis of bioactive molecules. In the present work, a straightforward and sustainable methodology for the one-pot synthesis of dihydropyrano [2,3-c] pyrazole has been developed using nitrogen-doped graphene oxide (NGO) as a solid carbocatalyst under neat condition. The presence of high-density different types of nitrogen on the basal plane and the edges of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…S. Ganesan and P. Suresh 110 hydrothermally synthesized nitrogen-doped graphene oxide (NGO) and investigated its application as a solid-base heterogeneous catalyst for pyranopyrazoles synthesis. Malononitrile, ethyl acetoacetate, hydrazine hydrate, and different functional groups of substituted aldehydes were combined in a condensation reaction under solvent-free conditions using a grinding technique, yielding high yields of pyranopyrazoles within 2 min ( Scheme 64 ).…”
Section: Green Solventsmentioning
confidence: 99%
“…S. Ganesan and P. Suresh 110 hydrothermally synthesized nitrogen-doped graphene oxide (NGO) and investigated its application as a solid-base heterogeneous catalyst for pyranopyrazoles synthesis. Malononitrile, ethyl acetoacetate, hydrazine hydrate, and different functional groups of substituted aldehydes were combined in a condensation reaction under solvent-free conditions using a grinding technique, yielding high yields of pyranopyrazoles within 2 min ( Scheme 64 ).…”
Section: Green Solventsmentioning
confidence: 99%
“…[60] A recent investigation by Ganesan et al reported the fabrication of nitrogen-doped graphene oxide (NGO) through a hydrothermal route and its use as a solid catalyst for facile and one-pot synthesis of dihydropyrano[2,3-c]pyrazole with good atom economy. [61] The nitrogen-rich graphene-based solid catalyst could be reused multiple times (∼ eight times) without any significant decrease in its catalytic activity, thereby providing a stable, solvent-free, sustainable, neat, and greener synthetic approach.…”
Section: Graphene-based Catalytic Platformsmentioning
confidence: 99%
“…Due to the large theoretical surface area of graphene (2630 m 2 /g), 22 several recent studies have been reported for the fabrication of more unique materials, such as graphene and graphene oxide (GO), as solid acid catalysts and their application in phenol degradation, 23 isoxazole and pyranopyrazole synthesis, 24 selective reduction of substituted nitro groups, 25 dihydropyrano [2,3‐c] pyrazole synthesis, 26 esterification of acetic acid with n ‐butanol, 27 and 2,4‐disubstituted quinoline synthesis 28 . Focusing on the saccharification of cellulose, a GO catalyst prepared through the modified Hummers' method and sonication was used in the saccharification of cellulose at 150°C for 24 h, resulting in a glucose yield of 21.4% 29 .…”
Section: Introductionmentioning
confidence: 99%